El dolor que nos une : el tercer caso del sargento Aector McAvoy - Mark, David John, 1977- (Nuevos tiempos (Madrid, Spain), 2015)
Detective Sergeant Aector McAvoy returns for another darkly enthralling case in Sorrow Bound, the third installment of David Mark's internationally acclaimed and bestselling series.